Pengaruh Fintech Payment Terhadap Perilaku Manajemen Keuangan Mahasiswa Yang Dimediasi Oleh Literasi Keuangan - Sholekha, Imroatus; Nurhidayah, Nurhidayah; Amin, Muhammad Sirojuddin (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to analyze the influence of Fintech Payment on Student Financial Management Behavior and the interaction of Financial Literacy on Fintech Payment and Student Financial Management Behavior. This type of research is quantitative research using MRA (Moderated Regression Analysis) data analysis techniques through statistical program social science (SPSS) version 25. The population of this study was student of faculty of economics and business with a sample of 86 students who used purposive sampling techniques. The results of this study show that fintech payment have a significant effect on student financial management behavior and financial literacy has a significant interaction with fintech payment and student financial management behavior. Keywords: Fintech Payment, Financial Management Behavior, Financial Literacy